Hubungan Motivasi Belajar Siswa Dengan Hasil Belajar PJOK Siswa Kelas XI SKO Bahteramas Tahun Ajaran 2023/2024 - Sahri, Basman, Resky Ana Abadi (LPPM Universitas Nahdlatul Ulama Sulawesi Tenggara, 2024)
Motivation is one of the factors that affect student success. A person will get the desired results in learning if there is a desire to learn in him. Motivation can serve as a product to achieve good results. A person will do activities or do learning because there is motivation in him. The existence of high motivation in learning will achieve optimal results.The purpose of the research achieved is to find out the learning motivation and learning outcomes of students at the Bahteramas Sports Talent School (SKO) grade XI for the 2023/2024 school year. Motivation as the main factor in learning is functioning, evoking, underpinning, and driving the act of learning. This research is a quantitative descriptive type with a correlation research design. According to the results of the study, when a student has high motivation will get high grades, on the contrary, those who have low motivation, seem indifferent, their attention is not directed to learning which as a result students will experience learning difficulties and their learning results will be low.